A Graphic Method for the Evaluation of Diagnostic Tests - Rossing, R. G.; Hatcher, W. E. (Methods of Information in Medicine, 1980)
The theory of decision-making has been previously applied to the evaluation of laboratory tests in clinical diagnosis taut the emphasis on formulae and equations has discouraged many physicians from attempting to understand the concept. This paper offers a graphic portrayal of the four possible decision outcomes : true negative, false negative, true positive and false positive. The presentation permits a graphic representation of the concepts of specificity, sensitivity, accuracy, predictive value of a laboratory test and information content as well as of the receiver-operating-characteristic (ROC) curve. It demonstrates why disease incidence has no effect upon specificity, sensitivity and the ROC curve but has a strong influence upon accuracy and information content and especially upon the predictive value of a positive laboratory test. The graphic method is applicable to theoretical distributions and to distributions based on actual laboratory data.
Keywords: Sensitivity; Specificity; Predictive Value; Receiver-operating-characteristic (ROC) Curve; Decision-Making; Information Content; Diagnostic Test